Biochemical Charcterization of Some Taro (Colocasia esculenta L. Schott) Germplasm in Ghana - R. Boampong; L. M. Aboagye; D. Nyadanu; M. E. Essilfie; R. Adu Amoah (Advances in Agriculture)
Corms of eighteen (18) genotypes comprising twelve (12) introduced and six (6) local genotypes were studied for their nutrient quality to provide information on their nutrient characteristics for a holistic development of the crop. The crop is known for its edible corms and leaves. Corms are boiled before eating and take a short time to cook as their carbohydrate structure is not complex. The leaves are eaten as vegetables. The crops were planted at Nobewam in the Ejisu-Juaben Municipality in the Ashanti Region of Ghana using the Randomized Complete Block Design (RCBD). The biochemical or nutritional analysis was done at Crop and Soil Sciences laboratory at Kwame Nkrumah University of Science and Technology (KNUST). Data were collected on the chemical and mineral compositions of the genotypes (corms). Variations were observed in both chemical and mineral characteristics. Carbohydrate content of the genotypes ranged from 62% to 76%; protein ranged from 13% to 25%; fibre ranged from 1% to 2%; calcium ranged from 0.29% to 0.72% and iron content ranged from 0.18 mg/100 g to 1.18 mg/100 g. Significant differences P<0.05 were observed in both chemical and mineral traits, indicating a higher degree of variability in the genotypes. Significant P<0.01 and positive correlations were observed between protein and energy levels; magnesium and iron; magnesium and calcium; and potassium and ash. The Principal Component Analysis (PCA) showed that the first component (PC1) accounted for 96% of variation. Some genotypes including; BL/SM/10, BL/SM/132, KA/019, SAO/020, BL/SM/151, BL/SM/80, BL/SM/116, BL/SM/16, and KA/035 possess desirable nutrient levels such as protein, fibre, carbohydrate, and iron which could be exploited for further development of taro in Ghana.